A Game-Theoretic Perspective on Coalition Formation - Ray, Debraj (Oxford University Press, 2007)
The formation of coalitions to achieve both collaborative and competitive goals is a phenomenon we see all around us. The list of examples of this phenomenon is long and varied: production cartels, political lobbies, customs unions, environmental coalitions, and ethnic alliances are just a few everyday instances. This book looks at coalition formation from the perspective of game theory. How are agreements determined? Which coalitions will form? And are such agreements invariably efficient from a social perspective? The book brings together developments in both cooperative and non-cooperative game theory to study the analytics of coalition formation and binding agreements. It concentrates on pure theory, but discusses several potential applications, such as oligopoly and the provision of public goods.